Response to dietary methionine supply of growing pigs fed daily tailored diets or fed according to a conventional phase feeding system - Remus, A. [UNESP]; Pomar, C.; Perondi, D. [UNESP]; Gobi, J. P. [UNESP]; Silva, W. C. da [UNESP]; Souza, L. J. de [UNESP]; Hauschild, L. [UNESP] (Elsevier B.V., 2019)
There is a large variation in nutrient requirements among pigs, and, therefore, feeding pigs individually with diets tailored daily or in groups with a single feed may require different nutrients inclusion rates. The objective of this study was to evaluate the effect of the Met inclusion rate on growth performance, carcass quality, and nutrition health variables of growing pigs fed within an individual precision feeding (IPF) or a conventional phase feeding (CPF) system. Sixty barrows weighing 25-50 kg of body weight of the same high-performance genotype were used. A 2 x 3 factorial arrangement of treatments with 2 main factors: (1) 2 feeding systems (IPF or CPF system), and (2) 3 Met inclusion rates (70, 100 or 130% of the ideal protein ratio of 0.30 Met:Lys) was used in a complete randomized design. Final body weight, average daily weight gain, feed efficiency, Met, and Cys intake, and loin depth were lower (P = 0.01) for IPF compared with CPF. Average daily gain increased linearly (P < 0.01) with increasing Met inclusion rates for IPF and it had no effect for CPF pigs. Average daily feed intake and backfat thickness were not different between feeding systems, yet both tended to increase linearly (P = 0.08) with the increase of Met inclusion rates. Lysine intake was lower (P < 0.01) in IPF compared with CPF pigs but Lys tended to increase quadratically (P = 0.06) with increasing Met inclusion rates for both systems. Plasma urea N was lower, and creatinine was higher in IPF pigs than in CPF pigs (P = 0.01), and both linearly increased (P = 0.01) with increasing Met inclusion rates. Alanine aminotransferase was higher (P = 0.02) in IPF than in CPF pigs, and remained unchanged with the increase of Met inclusion rate. Total plasma protein, triglycerides, and C-reactive protein did not differ between feeding systems neither among Met inclusion rates. These results indicate that Met to Lys ratio is underestimated for pigs fed with diets tailored daily, and the ideal protein profile might differ when pigs are fed in an IPF system or in a CPF system.
Keywords: Precision feeding; Amino acids requirements; Plasma biochemical variables; Growth performance; Precision livestock farming